Assessing and Developing Primary Education Curricula Based on Bloom’s Taxonomy: A Reconciliatory Approach - Nur Hafizah, Elma; Sigit Prasetyo (Program Studi PGMI, 2026)
Curriculum changes in Indonesia, from the pre-KTSP era to the Independent Curriculum, indicate a paradigm shift from a rote-based approach to student-centered learning. While aimed at improving critical thinking skills, these changes have raised concerns regarding a decline in academic competitiveness and depth of conceptual mastery. This study aims to encourage the dynamics of assessment and curriculum development at the elementary education level by promoting a reconciliation model through the consistent application of Bloom's Taxonomy. Using the Systematic Literature Review (SLR) method following the PRISMA protocol, 35 relevant articles from national and international baseline data (2015–2025) were analyzed in depth. The review results indicate that the majority of studies (88.6%) used a qualitative approach. Key findings revealed inconsistencies in the integration of all cognitive levels of Bloom's Taxonomy (C1–C6) in existing assessment instruments. Most assessment practices still tend to focus on lower cognitive domains, thus not explicitly and systematically measuring higher-order thinking skills (HRT) in a comprehensive manner. Furthermore, significant challenges were identified for teachers in implementing an integrated curriculum without sacrificing deep knowledge structures. The implications of this research offer a